Czech Republic : Pilot Assessment of Governance of the Insurance Sector - World Bank (Washington, DC, 2013)
This assessment of the governance of the Czech insurance sector has three objectives: (1) develop a set of best practice benchmarks for assessing the governance of insurance sectors in the Europe and Central Asia Region and elsewhere, (2) conduct a trial assessment of the Czech insurance governance framework against these benchmarks, and (3) provide recommendations on ways of further improving the corporate governance of the Czech insurance sector. The benchmarks and the assessment are found in Annex I and a list of recommendations is presented in Annex II. As this is a pilot assessment, the final report should be seen as no more than a work-in-progress. Nevertheless, it is expected that it will play a useful role in contributing to guidelines for strong corporate governance of insurers in both developed and emerging markets. It could also lay the basis for further governance-based reforms of the Czech insurance sector and provide a baseline assessment for measurement of the reforms.